Die Fremdheit der Tiere Zur theologischen Konstruktion und Dekonstruktion des Anderen - Herdramm, Henrike (animate theologies, 2023)
The theology's forgetfulness of animals makes it clear that it is time to rethink animals theologically and to overcome the prevailing anthropocentrism. For this, a deconstruction of the Other is necessary in order to critically question established legitimations and theological presuppositions regarding violence against animals. In this volume from the series "Animate Theologies", the systematically constructed otherness of animals and their entanglement in theological and secular patterns of thought and action are deconstructed and critically questioned in order to overcome the exclusion of animals from theology. In doing so, (intersectional) devaluation mechanisms are analyzed, which are used to legitimize a violent treatment of non-human animals and are thereby rarely consciously perceived or questioned. It is only this deconstruction of established relations that makes it possible to unfold the theological potential of animals.